Structural changes of antitoxin HigA from Shigella flexneri by binding of its cognate toxin HigB - Yoon, Won Su; Seok, Seung Hyeon; Won, Hyung Sik; Cho, Taehwan; Lee, Sang Jae; Seo, Min Duk (International Journal of Biological Macromolecules, 2019)
In toxin-antitoxin systems, many antitoxin proteins that neutralize their cognate toxin proteins also bind to DNA to repress transcription, and the DNA-binding affinity of the antitoxin is affected by its toxin. We solved crystal structures of the antitoxin HigA (apo-SfHigA) and its complex with the toxin HigB (SfHigBA) from Shigella flexneri. The apo-SfHigA shows a distinctive V-shaped homodimeric conformation with sequestered N-domains having a novel fold. SfHigBA appears as a heterotetramer formed by N-terminal dimerization of SfHigB-bound SfHigA molecules. The conformational change in SfHigA upon SfHigB binding is mediated by rigid-body movements of its C-domains, which accompanied an overall conformational change from wide V-shaped to narrow V-shaped dimer. Consequently, the two putative DNA-binding helices (α7 in each subunit) are repositioned to a conformation more compatible with canonical homodimeric DNA-binding proteins containing HTH motifs. Collectively, this study demonstrates a conformational change in an antitoxin protein, which occurs upon toxin binding and is responsible for regulating antitoxin DNA binding.
Keywords: Amino Acid Sequence; Antitoxins; DNA; Models, Molecular; Protein Binding; Protein Multimerization; Protein Structure, Quaternary; Shigella flexneri; Toxins, Biological; Conformational change; DNA binding; HigBA; Toxin-antitoxin system; X-ray crystallography